Integrated Education to Improve Treatment Adherence for Type 2 Diabetes Mellitus Patients in Makassar - Suprapto Suprapto; Karlyna Bte Muhammad; Rahman Rahman; M. Khalid Fredy Saputra (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2026)
Treatment adherence remains a major challenge in the management of Type 2 Diabetes Mellitus (T2DM), particularly in community and primary health care settings. In Makassar, Indonesia, inadequate patient knowledge, negative attitudes toward long-term therapy, and fragmented health education contribute to suboptimal adherence and increase the risk of diabetes-related complications. This community service program aimed to improve treatment adherence among patients with T2DM through an integrated education approach. The program was implemented using a structured, participatory method involving five stages: situational analysis and coordination, participant recruitment and baseline assessment, integrated education intervention, mentoring and reinforcement, and evaluation and reflection. A total of 30 adult patients with T2DM participated in the program. Educational activities were delivered through interactive lectures, group discussions, practical demonstrations, and individualized counseling, focusing on medication adherence, dosage and administration, nutritional support, supplement safety, and the role of micronutrients in diabetes management. Program effectiveness was evaluated using pre- and post-intervention assessments of participants’ knowledge and adherence-related understanding. The results demonstrated a substantial improvement in knowledge across all assessed domains following the intervention. These findings indicate that integrated education is an effective strategy for strengthening patient understanding and supporting improved treatment adherence among individuals with Type 2 Diabetes Mellitus at the community level